Evaluation of Herbal Methionine Source in Broiler Diets - Yuan, J.; Karimi, A.J.; Goodgame, S.D.; Lu, C.; Mussini, F.J.; Waldroup , P.W. (International Journal of Poultry Science, 2012)
A study was conducted to evaluate an herbal methionine replacement product in diets for young broiler chicks. A corn-soybean meal diet that was complete in all respects but methionine was prepared and divided into three aliquots. One was supplemented with 0.30% DL methionine and another was supplemented with the herbal methionine replacement product. Each of these was then blended with the unsupplemented basal diet to provide diets with 0, 0.05, 0.10, 0.15, 0.20, 0.25 and 0.30% of either DL methionine or the herbal methionine replacement product. Each diet was fed to twelve pens of five male broiler type chicks each in electrically heated battery brooders. The diets and tap water were provided for ad libitum feeding from day of hatch to 18 d of age. Analysis of the diets indicated that the methionine activity of the diets with DL methionine was close to expected values but no apparent increase in analyzed methionine activity in diets supplemented with the herbal methionine replacement product. Body weight gain and feed conversion of birds fed the diets with DL methionine were significantly superior to that of birds fed the diets with the herbal methionine replacement product. No significant differences were observed between birds fed the two products for weight of digestive or immune organs when expressed as a percentage of body weight. These data suggest that the herbal methionine replacement product is not suitable for use as a methionine source in diets for young broiler chicks.